The effectiveness of essential oils as a biofungicide and potassium fertilizers in control of rubber leaf fall disease (Corynespora sp.) - Putra S.; Ferry Y.; Heryana N. (E3S Web of Conferences, 2023)
Corynespora causes leaf fall disease in rubber plants. Control can be done with bio fungicides and potassium fertilizer. This study aims to determine the effectiveness of essential oils and potassium fertilizer in controlling rubber leaf fall disease. The research was conducted from January to December 2018 in Landak Regency, West Kalimantan. The study used a randomized block design with 13 treatments repeated 3 times. The treatment is without biofungicide and KCl, citronella oil + (KCl 250 g, 312.5 g, and KCl 375 g), clove oil + (KCl 250 g, 312.5 g, and 375 g), liquid smoke + (KCl 250 g, 312.5 g, and 375 g), chemical fungicides (mancozeb) + (KCl 250 g, 312.5 g, and 375 g). The results showed that citronella oil, clove oil, and liquid smoke had the same inhibitory power as chemical fungicides. The combination of citronella oil with fertilizer KCl 312.5 g/plant/year and clove oil with KCl 375 g/plant/year can reduce the intensity of Corynospora attack up to 7.33% with inhibition of rubber leaf fall disease reaching 90.09% and can maintain yield of 28.1-28.3 g/tapping (94.33%). KCl fertilizer increased the lignin content of rubber leaves by 22.63%.